Human Resource Management Practices and Job Satisfaction: Basis for Development of a Teacher Retention Framework - Mondejar, Hans Christian U.; Asio, John Mark R. (Future Science / FSH-PH Publications, 2022)
The objective of this research paper is to examine the association between Human Resource Management (HRM) practices and teachers' Job Satisfaction (JS) of private academic institutions in Olongapo City, Philippines. The investigators used a descriptive-correlation research design among 170 conveniently chosen respondents. The study used an adopted and modified research instrument wherein the gathered data underwent descriptive and inferential analysis. The study revealed that private academic institutions practice recruitment and selection processes, evaluate employee performance, provide training and development, appropriate compensation, career planning opportunities, and employee safety, health, and welfare. Furthermore, respondents were satisfied with their supervisors, coworkers, working conditions, compensation and responsibilities; job itself, advancement, security, and recognition. Inferential analysis revealed that the association between HRM practices and job satisfaction is highly significant. The investigators used human resources management practices and job satisfaction to develop a teacher retention framework based on these results.